Diagnosis and treatment of upper limb apraxia - Dovern, A. (Springer-Verlag, 2012)
Upper limb apraxia, a disorder of higher motor cognition, is a common consequence of left-hemispheric stroke. Contrary to common assumption, apraxic deficits not only manifest themselves during clinical testing but also have delirious effects on the patients’ everyday life and rehabilitation. Thus, a reliable diagnosis and efficient treatment of upper limb apraxia is important to improve the patients’ prognosis after stroke. Nevertheless, to date, upper limb apraxia is still an underdiagnosed and ill-treated entity. Based on a systematic literature search, this review summarizes the current tools of diagnosis and treatment strategies for upper limb apraxia. It furthermore provides clinicians with graded recommendations. In particular, a short screening test for apraxia, and a more comprehensive diagnostic apraxia test for clinical use are recommended. Although currently only a few randomized controlled studies investigate the efficacy of different apraxia treatments, the gesture training suggested by Smania and colleagues can be recommended for the therapy of apraxia, the effects of which were shown to extend to activities of daily living and to persist for at least 2 months after completion of the training. This review aims at directing the reader’s attention to the ecological relevance of apraxia. Moreover, it provides clinicians with appropriate tools for the reliable diagnosis and effective treatment of apraxia. Nevertheless, this review also highlights the need for further research into how to improve diagnosis of apraxia based on neuropsychological models and to develop new therapeutic strategies.